1993
DOI: 10.1111/j.1432-1033.1993.tb17861.x
|View full text |Cite
|
Sign up to set email alerts
|

The promoter and intron/exon structure of the human and mouse β3‐adrenergic‐receptor genes

Abstract: Transcription-start sites for the mouse and human beta 3-adrenergic-receptor mRNA have been localized in a region comprised between 150 and 200 nucleotides 5' from the ATG translation-start codon. Motifs potentially implicated in heterologous regulation of beta 3-adrenergic-receptor expression by glucocorticoids and by beta-adrenergic agonists have been identified upstream from these cap sites. In mouse, a second mRNA initiation region is postulated to exist further upstream. Comparison of the nucleotide seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0
2

Year Published

1994
1994
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 28 publications
(50 reference statements)
0
53
0
2
Order By: Relevance
“…Another possibility is the existence of a comparatively small pool of ␤ 3 -AR mRNA, ~20% of the total, that is more stable. An alternate ␤ 3 -AR mRNA splice variant has been identified in mouse BAT and WAT (24) and also in 3T3-F442A cells (34). Our assay does not distinguish these variants, and even though Granneman and Lahners (34) did not find that they are differentially regulated by cAMP, the possibility that one of them has a longer life span in HIB-1B cells remains to be tested.…”
Section: Discussionmentioning
confidence: 85%
“…Another possibility is the existence of a comparatively small pool of ␤ 3 -AR mRNA, ~20% of the total, that is more stable. An alternate ␤ 3 -AR mRNA splice variant has been identified in mouse BAT and WAT (24) and also in 3T3-F442A cells (34). Our assay does not distinguish these variants, and even though Granneman and Lahners (34) did not find that they are differentially regulated by cAMP, the possibility that one of them has a longer life span in HIB-1B cells remains to be tested.…”
Section: Discussionmentioning
confidence: 85%
“…It was reported that all three isoforms of RAMPs, RAMP-1, -2, and -3, are expressed in adipose tissue (26). The β3-adrenergic receptor, predominantly expressed in adipocytes, mediates the catecholamine action on lipolysis, and there are cAMP-response elements in the promoter of the β3-adrenergic receptor gene (27,28). It is therefore tempting to speculate that AM may modulate the expression of β3-adrenergic receptors via the cAMP pathway as an autocrine and/or paracrine factor, and this matter will require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The mouse b 3 -adrenoceptor (AR) gene contains two introns, both of which undergo alternate splicing (van Spronsen et al, 1993;Granneman & Lahners, 1995;Evans et al, 1999). Splicing of intron A at a novel acceptor site 100 bp upstream from the previously characterized start of exon 2 results in the production of mRNA encoding a b 3 -AR variant, termed the b 3b -AR.…”
Section: Introductionmentioning
confidence: 99%
“…This receptor has a unique Cterminal tail, with 17 amino acids (SSLLREPRHLYTCLb 3b -AR transcripts in brown adipose tissue (BAT), and the highest in hypothalamus (Evans et al, 1999). Previous studies in mice have shown that alternate splice acceptor sites result in the generation of two b 3 -AR transcripts that di er in the 3' untranslated regions (van Spronsen et al, 1993: Granneman & Lahners, 1995. These transcripts have di ering tissue expression in WAT and BAT, with the shorter transcript predominant in WAT, and the longer transcript in BAT.…”
Section: Introductionmentioning
confidence: 99%